Effects of Environmental Enrichment in Maternally Separated Rats: Age and Sex-Specific Outcomes - Doreste-Mendez, Raura; Ríos-Ruiz, Efraín J.; Rivera-López, Leslie L.; Gutierrez, Alfredo; Torres-Reveron, Annelyn (Frontiers in Behavioral Neuroscience, 2019)
Maternal separation (MS) early in life is related to an increase in anxiety and depressive-like behaviors and neurobiological alterations mostly related to alterations in HPA axis reactivity. Environmental enrichment (EE) has been used to ameliorate the effects of MS. However, the outcomes of this intervention at different developmental periods after MS have not been studied. We subjected male and female Sprague Dawley pups to maternal separation and subsequently compared the effects of EE started either in the pre-pubertal period (postnatal day 22) or adulthood (postnatal day 78). Anxiety and depressive-like behaviors as well as in hippocampal synaptic density and basal corticosterone, oxytocin, and vasopressin levels were measured. Our results support the beneficial effects of adulthood EE in decreasing anxiety in males as well as promoting synaptic density in ventral hippocampal CA3. Males displayed higher levels of vasopressin while females displayed higher oxytocin, with no changes in basal corticosterone for any group after EE.